Adolescents in Virtual Forum: Playing, Socializing, or Engaging in Public Issues? - S. Rouli Manalu; Rafky Muhammad (Komunikator, 2021)
This research examines how adolescents perceive their memberships and involvement in virtual forums and whether the young generations see this involvement facilitate their engagement with public issues surrounding them. The increase of political discussions and political debates over the Internet and social media in Indonesia has become the trigger of this research to see whether adolescents as the group of new voters, even first-time voters, use virtual forums to be critically engaged in a discussion of public issues. Alternatively, this research would see whether their engagement in virtual communities is mainly related to entertainment, social connections, and other matters not directly related to politics and discussion of public issues. By interviewing a group of adolescents from at least eight provinces in Indonesia, this research examines the phenomenological experiences regarding their action, perception, and evaluation of their involvement through various virtual communities. This research highlights the importance of understanding adolescents’ experiences in virtual communities to understand better their tendency and attitude in relating to issues in their online and offline environments.